Salvage total glossectomy and total glosso-laryngectomy: Are they worth it? A GETTEC French multicenter study. (July 2022) - Mazerolle, Paul; Fuchsmann, Carine; Schultz, Philippe; Benmoussa, Nadia; Malard, Olivier; Bozec, Alexandre; Deneuve, Sophie; Folia, Mireille; Perréard, Marion; Lasne-Cardon, Audrey; Chabrillac, Emilien; Vergez, Sébastien; et al.
Highlights: Total glossectomy and total glosso-laryngectomy are controversial procedures. There is no consensus regarding their rationale in salvage surgery. Overall Survivall and Disease Free Survival were estimated at 19 and 10 months. After a median follow-up of 90 months, 24% of patients were alive and disease-free. We noted an important gastric tube dependency in both groups. Abstract: Background: Salvage total glossectomy (TG) or total glosso-laryngectomy (TGL) remain controversial, as highly morbid procedures. The objective was to describe oncological and functional outcomes after salvage TG or TGL. Methods: We performed a multicenter retrospective study, including patients with previous neck irradiation undergoing TG or TGL for squamous cell carcinoma involving the base of tongue. Results: We included 42 patients: 27 in the TG group and 15 in the TGL group. For the entire cohort, median OS and DFS were estimated at 19 months (95% IC [14–44]) and 10 months (95% IC [7–13]) respectively, with no difference between the two groups. After a median follow-up of 90 months, 10 patients (24%) were alive and free of disease. Att he end of follow-up, we noted a gastrostomy dependency of 89% and 87 %respectively in the TG and TGL group, and 48% of patients in the TG group had a tracheotomy. Conclusion: Although local control is difficult to achieve after salvage TG or TGL, these procedures are associated with acceptable survival and chance of cure for a last-resort situation. TG and TGL can be proposed in selected motivated patients after careful shared decision-making.